2019
DOI: 10.1111/eje.12479
|View full text |Cite
|
Sign up to set email alerts
|

How does dyslexia impact on the educational experiences of healthcare students? A qualitative study

Abstract: Learning disabilities (LDs) is a generic term and comprises a heterogeneous group of disorders which manifest with an impairment of intellectual or social functioning and affects the way an individual learns new things in any area of their life. 1,2 Specific LDs include conditions such as dyslexia, development coordination disorder (DCD), dyscalculia, attention deficit disorder (ADD) and attention deficit hyperactivity disorder (ADHD). 3,4 Dyslexia constitutes the most common form of LD and affects up to 10% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Negative attitudes in nursing were also reported by Shpigelman et al (2016), who found that nursing students held negative attitudes toward colleagues with disabilities, as well as toward people with disabilities in general. Despite the findings of negative attitudes, however, Ali et al (2020) reported some positive placement experiences and found that students with disabilities had no difficulties in communicating with patients or learning practical clinical skills. However, students reported difficulties with writing up clinical notes.…”
Section: Discipline-specific Barriers and Facilitatorsmentioning
confidence: 91%
See 3 more Smart Citations
“…Negative attitudes in nursing were also reported by Shpigelman et al (2016), who found that nursing students held negative attitudes toward colleagues with disabilities, as well as toward people with disabilities in general. Despite the findings of negative attitudes, however, Ali et al (2020) reported some positive placement experiences and found that students with disabilities had no difficulties in communicating with patients or learning practical clinical skills. However, students reported difficulties with writing up clinical notes.…”
Section: Discipline-specific Barriers and Facilitatorsmentioning
confidence: 91%
“…The most frequently reported barrier among students and graduates was their concern over disclosing a disability (Stein, 2012;Atkinson and Hutchinson, 2013;Walker et al, 2013;Luckowski, 2014;Cunnah, 2015;Easterbrook et al, 2015;Nolan et al, 2015;Clouder et al, 2016;Nolan and Gleeson, 2017;Vlachou and Papananou, 2018;Ali et al, 2020;Grimes et al, 2020;Saltes, 2020;Vincent, 2020;Odame et al, 2021;Shpigelman et al, 2021;Sullivan, 2021). These concerns stemmed mainly from the fear that disclosure would result in stigma from peers, faculty staff, placement educators, and/or employers.…”
Section: Disclosurementioning
confidence: 99%
See 2 more Smart Citations
“…Dyslexia is a learning disability that affects up to 10% of the global population (Ali et al, 2020 ). It is sometimes misdiagnosed as a visual-perceptual disorder, although it is a language-based reading impairment.…”
Section: Introductionmentioning
confidence: 99%